The UK Crop Microbiome Cryobank: a utility and model for supporting Phytobiomes research - Matthew J. Ryan; Tim H. Mauchline; Jacob G. Malone; Susan Jones; Catriona M. A. Thompson; J. Miguel Bonnin; Helen Stewart; Payton T. O. Yau; Rodrigo G. Taketani; Ian M. Clark; Nicola Holden (CABI Agriculture and Bioscience)
Abstract Plant microbiomes are the microbial communities essential to the functioning of the phytobiome—the system that consist of plants, their environment, and their associated communities of organisms. A healthy, functional phytobiome is critical to crop health, improved yields and quality food. However, crop microbiomes are relatively under-researched, and this is associated with a fundamental need to underpin phytobiome research through the provision of a supporting infrastructure. The UK Crop Microbiome Cryobank (UKCMC) project is developing a unique, integrated and open-access resource to enable the development of solutions to improve soil and crop health. Six economically important crops (Barley, Fava Bean, Oats, Oil Seed Rape, Sugar Beet and Wheat) are targeted, and the methods as well as data outputs will underpin research activity both in the UK and internationally. This manuscript describes the approaches being taken, from characterisation, cryopreservation and analysis of the crop microbiome through to potential applications. We believe that the model research framework proposed is transferable to different crop and soil systems, acting not only as a mechanism to conserve biodiversity, but as a potential facilitator of sustainable agriculture systems.